PengaruhPenerapanManajemenResikoTerhadap Return On Equity Di Perusahaan Perbankan - Adistriana, Irna; Anastasya, Cella; Rahmawati, Nanda Putri (CV. ITTC INDONESIA, 2022)
This study aims to find out how the application of Risk Management in banks that experience problems such as bad debts, as well as to determine the influence between Operating Costs and Operating Income (BOPO), Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL) on the Return on Equity (ROE) of Banking Companies, both partially and simultaneously. This study consists of one dependent variable, namely Return on Equity (ROE) and three independent variables, namely Operating Costs and Operating Income (BOPO), Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL). The type of research used is Associative Quantitative Research. The population in this study used secondary data obtained from the company's annual report focused on the private conventional banking sector from 2017 to 2021 listed on the Indonesia Stock Exchange. This secondary data was obtained by researchers from the IDN Financials Website. The test results simultaneously showed that all independent variables of Operating Expenses and Operating Income (BOPO), Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL) together had a significant positive effect on the dependent variable Return on Equity (ROE). This is proven based on the calculated F value of 61.11716 and the Ftabel of 2.81 or in other words (61.11716 > 2.81) and has a Prob value (F-statistic) of 0.000000.